AUDIT QUALITY AND REAL EARNINGS MANAGEMENT: EVIDENCE FROM TUNISIAN BANKS - Zgarni, Amina; Chikhaoui, Monia (Indian Journal of Finance and Banking, 2022)
The beginning of the 21st century was marked by a multitude of financial scandals, notably the Enron affair in 2001 and the fall of the auditing firm Arthur Andersen (2002). Such scandals have called into question of the financial reporting quality. The main cause of these scandals was the failure of the external audit quality which is considered crucial to ensure the reliability and relevance of accounting information. Moreover, following the promulgation of the SOX law (2002), managers tend rather towards the real activities manipulation to avoid the detection of the accounting earnings management. In fact, managers can resort to certain adjustments whose opportunistic or optimal nature is difficult to discern by auditors, in particular the reduction in selling prices, the granting of more lenient credit terms, overproduction and the reduction or postponement of research and development (R&D) and advertising expenditure. This study therefore aims to show the role that external audit quality can play in limiting real activities manipulation and therefore in the quality of accounting information. For this, we conducted an empirical study with a sample of the main. Tunisian commercial banks observed over a period from 2006 to 2019, using the panel data method. The results indicate that the presence of a reputable auditor limits real earnings management. However, the results show that the tenure of auditors increases these discretionary practices.JEL Classification Codes: M41, M42, G21.